Blockchain & distributed financial data. Issue 6 (5th June 2019) - Nikbakht, Ehsan; Shahrokhi, Manuchehr; Corriette, Alford
Abstract : Purpose: The purpose of this paper is to investigate the emergence of blockchain to determine its feasibility for electronic transfer payments. An integrated conceptual framework is developed for blockchain electronic transfer. The three "markers" of classic money (store of value, medium of exchange and unit of account and efficiency) are assessed in the case of blockchain technology. A survey is also conducted among the executives of financial vs manufacturing sectors with respect to five major variables for the emerging distributed financial data based on blockchain. Design/methodology/approach: Conducting a literature review and using prior knowledge from the works of those well-versed and knowledgeable in the field. This research is also supported by collecting and analyzing the results of a behavioral survey of the executives in two different industries. Findings: Blockchain technology has the potential to have widespread change in how firms operate and implement a new method for electronic payments transfer through cryptocurrencies. Although the community for blockchain technology is deregulated and has drawbacks, it is expected that the limitations will gradually be mitigated through its growth. The results of the behavioral survey show that there are significant differences between the expectations/perceptions of participants in the sectors of finance vs manufacturing. Namely, the knowledge/awareness of participants about blockchain, the value-added convenience for end users, and participants' willingness to embracing and accepting new applications are significantly different between the two sectors. Originality/value: The reach and applications for Blockchain are not limited to business or any particular sector. Blockchain technology may contribute to the operations of different types of organizations and industry sectors. Since the perception of participants about blockchain is different between selected industries, this research suggests the need for more education and building awareness among the participants in different sectors of the economy.